PENGARUH LATIHAN REACTIVE JUMP TERHADAP POWER OTOT TUNGKAI SISWA EKSTRAKURIKULER SMA AN NAS PEKANBARU - Mahmud, Novri; Wijayanti, Ni Putu Nita; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problems in the residence of the student exctracurricular SMA An Naas Pekanbaru is still of the student exstracurricular Pekanbaru such, it is seen to be done from various tests and official competitions, so the lack of maneuverability is a factor contributing to the defeat. The purpose of this research was to observe the effect of practice reactive jump for legs muscle strength on student extracurricular SMA An Naas Pekanbaru with respondents 16 people. Sampling techniques using total sampling, where the total population is sampled. Data collection techniques derived from the pre-test and post test. Instrument in this research using Vertical Jump Test to see the power legs muscle. Analyses were performed using t-test. Based on data analysis and discussion it can be concluded that there is significant effect from a exercises reactive jump for the power legs muscle Pekanbaru as evidence by Ttest 12.05 and Ttable 1.75. it means Ttest > Ttable at the level of α=0.05Keyword : reactive jump, legs muscle strenght,volyballl